The Spillover of US Immigration Policy on Citizens and Permanent Residents of Mexican Descent: How Internalizing “Illegality” Impacts Public Health in the Borderlands - Sabo, Samantha; Lee, Alison Elizabeth (Frontiers in Public Health, 2015)
Background The militarization of the US–Mexico border region exacerbates the process of “Othering” Latino immigrants – as “illegal aliens.” The internalization of “illegality” can manifest as a sense of “undeservingness” of legal protection in the population and be detrimental on a biopsychological level. Objective We explore the impacts of “illegality” among a population of US citizen and permanent resident farmworkers of Mexican descent. We do so through the lens of immigration enforcement-related stress and the ability to file formal complaints of discrimination and mistreatment perpetrated by local immigration enforcement agents, including local police authorized to enforce immigration law. Methods Drawing from cross-sectional data gathered through the National Institute of Occupation Safety and Health, “Challenges to Farmworker Health at the US–Mexico Border” study, a community-based participatory research project conducted at the Arizona–Sonora border, we compared Arizona resident farmworkers (N = 349) to Mexico-based farmworkers (N = 140) or Transnational farmworkers who cross the US–Mexico border daily or weekly to work in US agriculture. Results Both samples of farmworkers experience significant levels of stress in anticipation of encounters with immigration officials. Fear was cited as the greatest factor preventing individuals from reporting immigration abuses. The groups varied slightly in the relative weight attributed to different types of fear. Conclusion The militarization of the border has consequences for individuals who are not the target of immigration enforcement. These spillover effects cause harm to farmworkers in multiple ways. Multi-institutional and community-centered systems for reporting immigration-related victimization is required. Applied participatory research with affected communities can mitigate the public health effects of state-sponsored immigration discrimination and violence among US citizen and permanent residents.